Pengembangan Media Pop Up Book (Makanan Bergizi) Untuk Stimulasi Pengenalan Makanan Sehat Bergizi Pada Anak Usia 4-6 Tahun - Sapil, Nursin; Hardianti, Hardianti (Civiliza Publishing, Indonesia., 2024)
This study aims to develop and evaluate the effectiveness of nutritious food-based pop-up book learning media for children aged 4-6 years at PAUD Ar-Rahman Bina Insani, Ternate City. This research method uses a research and development (R&D) approach with a learning media design and evaluation method. This media is designed to improve children's knowledge about healthy and nutritious food through an interesting and interactive approach. The development method involves validation by material experts and media experts, as well as trials with children at the PAUD. The findings of this study show that the validation results by material experts showed a score of 80%, indicating that this media is feasible in terms of educational content. Validation by media experts obtained a score of 89.2%, indicating that the media design and visualization are very feasible. Children's responses to this media were very positive with a score of 93.3%, indicating that this media is interesting and improves their understanding of nutrition. This study concludes that nutritious food-based pop-up books are effective in teaching nutritional concepts in a fun and interesting way. This media can be an innovative solution to improve nutrition education in PAUD and is recommended for use in the early childhood education curriculum. Further development and long-term studies are needed to assess the impact of this media on children's eating habits in more depth.